Literacy Socialization in Social Media is Good for Students - Safaruddin Safaruddin; Riskasari Riskasari; Andi Muhammad Ishak Ismail (Yayasan Cendekiawan Digital Indonesia, 2024)
The rapid advancement of technology and the internet has greatly facilitated human interaction and communication. However, along with its benefits, the rapid expansion of the internet has also brought about negative consequences such as cybersex, cyberbullying, and online radicalization. Therefore, it is imperative to promote the judicious use of social media to enhance awareness, particularly among school children, about the hazards of its misuse. The community service program at SMP Negeri 2 Mandalle is designed to enhance students' comprehension of utilizing social media appropriately and responsibly. Through this initiative, students receive comprehensive explanations and engage in discussions about both the advantages and risks associated with social media usage. The students at SMP Negeri 2 Mandalle demonstrate a deep understanding of the perils associated with social media usage. This is evident from the smooth execution of the community service activity, which aligns seamlessly with its intended objectives. The activities encompass a diverse range, including understanding the nature of social media, recognizing its adverse effects, determining appropriate usage times, and establishing age-appropriate boundaries for social media engagement.